Statistics / James T. McClave, Frank H. Dietrich II, Terry Sincich - McClave, James T. (Prentice Hall, 1997)
An introduction to statistics which features explanations, reinforced with examples and applications. Among the applications are case studies using actual research data to demonstrate important concepts and techniques. Examples incorporate more computer techniques and draw on a wide range of material from psychology, political science, criminal justice and other social sciences. The text features a treatment of regression analysis: simple regression, multiple regression and model building, with a selection of "real world" case studies and over 1,000 exercises. There are also sample print-outs for leading statistical software packages including MINITAB, SAS, and SPSS.